Harnessing Innovation: Exploring the Impact of Market Orientation and Firm Resources on Performance in West Sumatra's Event and Party Services - Sari, Chintia Wulan; Yeni, Yulia Hendri; Pujani, Vera (Yayasan Riset dan Pengembangan Intelektual, 2024)
Marriage holds a sacred significance in Minangkabau culture, representing the pinnacle of the life cycle, where customs transcend mere entertainment to embody profound philosophical and cultural values. Despite the substantial opportunities for party service businesses in West Sumatra, the performance of firms in this sector often falls short of expectations. Observations reveal recurring issues, including vendor delays and dissatisfaction with service quality in areas such as decoration, photography, videography, and catering. These problems are primarily attributed to inadequate resource management and poor strategic decision-making. This study employs explanatory research with a quantitative approach, utilizing hypothesis testing to examine the relationships among market orientation, firm resources, innovation, and firm performance. The validity and reliability of the questionnaire instrument were confirmed to ensure accurate data analysis. The findings demonstrate that, within the context of party service businesses in West Sumatra, both market orientation and firm resources significantly impact innovation and firm performance directly; however, innovation does not serve as an effective mediator in this relationship.